A comprehensive review of the prospects for future hydrogen storage in materials-application and outstanding issues - Dewangan, Sheetal Kumar; Mohan, Man; Kumar, Vinod; Sharma, Ashutosh; Ahn, Byungmin (International Journal of Energy Research, 2022)
The ongoing population explosion has led to the rapid consumption of different energy sources. The continuous demand for energy and its associated services for socio-economic development is concerning due to the reduction of natural energy sources. Therefore, research to explore clean and sustainable energy sources to fulfill this energy demand has continuously been conducted over the past decades. Hydrogen is widely accepted as a possible energy carrier owing to its advantages, such as ease of availability, renewability, and environmentally friendly nature. Hydrogen storage in the liquid or gaseous form poses safety and transportation challenges. In this context, metal hydrides are a vital solution. This review article discusses unique collections of HEA-based metal hydrides for the first time in conjunction with conventional metal hydrides. This article can potentially guide the materials research community in understanding the current challenges associated with designing novel hydrogen storage alloys from a clean energy perspective and their applications. The review suggests improving the thermodynamics and hydrogen reaction kinetics to enhance hydrogen storage capacity. Finally, the global developing trends are reviewed and critical challenges and promising opportunities are identified. Highlights: Essential aspects of various alloys and their hydrides are analyzed. This review supports the utilization of hydrogen as clean energy fuel and its possible storage measures. The review provides an imperative connection of the metal hydrides, including emerging high-entropy alloy hydrides, with renewable and sustainable energy. Metal hydrides are an economic option for hydrogen-based energy applications. This review focuses on present issues and the prospective application of hydrogen storage.
Keywords: Clean energy; Continuous demand; Different energy sources; Energy; Environment; Green energy; High entropy alloys; Material application; Metal-hydrides; Population explosion; environment; green energy; high-entropy alloy; hydrogen; metal hydrides